Interactive STEAM-Based E-Modules in Chemistry Education: Implementation and Impact - Kartini Rahman Nisa; Wahyuningsih; Sri Astuti Rahman Coa; Jayadin; Kristina Tresia Leto (The Indonesian Institute of Science and Technology Research, 2026)
The abstract nature of chemical concepts, which are often intangible and not directly observable, makes chemistry learning challenging and can reduce overall learning quality. Integrating technology with interdisciplinary approaches, such as STEAM-based interactive e-modules, offers a promising solution to enhance chemistry education. This study aims to systematically map the implementation of STEAM-based e-modules and examine their impact on chemistry learning. A literature review method was employed, sourcing data from Google Scholar and Scopus using the keywords